Synthesis of 1,4-Dioxaspiro[4.4] and 1,4-Dioxaspiro[4.5] Novel Compounds from Oleic Acid as Potential Biolubricant - Yehezkiel Steven Kurniawan; Yudha Ramanda; Kevin Thomas; Hendra Hendra; Tutik Dwi Wahyuningsih (Indonesian Journal of Chemistry, 2017)
Two 1,4-dioxaspiro novel compounds which derivated from methyl 9,10-dihydroxyoctadecanoate (MDHO) with cyclopentanone and cyclohexanone had been synthesized by a sonochemical method in the presence of montmorillonite KSF catalyst. The MDHO compound had been prepared from 9,10-dihydroxyoctadecanoic acid (DHOA) and methanol. Meanwhile, DHOA was synthesized by hydroxylation of oleic acid with the solution of 1% KMnO4 under basic condition. The structures of the products were confirmed by FTIR, GC-MS, 1H-NMR, and 13C-NMR spectrometers. Hydroxylation reaction of oleic acid gave DHOA as a white solid powder in 46.52% yield (m.p. 131-132 °C). On the other side, esterification reaction via sonochemical method between DHOA and methanol gave MDHO as a white powder in 93.80% yield (m.p. 80-81 °C). The use of cyclopentanone in 45 min sonochemical method gave methyl 8-(3-octyl-1,4-dioxaspiro[4.4]nonan-2-yl)octanoate as a yellow viscous liquid in 50.51% yield. The other compound, methyl 8-(3-octyl-1,4-dioxaspiro[4.5]decan-2-yl)octanoate as yellow viscous liquid had been synthesized by similar method with cyclohexanone via the sonochemical method in 45.12% yield. From physicochemical properties, i.e. density, total acid number, total base number, and iodine value, gave the conclusion that these novel compounds are potential biolubricant candidates to be developed.